Divergent soil P accrual in ectomycorrhizal and arbuscular mycorrhizal trees: insights from a common garden experiment in subtropical China - Lian, Pingping; Xu, Linglin; Yang, Liuming; Yue, Kai; Peñuelas, Josep (Frontiers in Plant Science, 2024)
Tree species establish mycorrhizal associations with both ectomycorrhizal (EM) and arbuscular mycorrhizal fungi (AM), which play crucial roles in facilitating plant phosphorus (P) acquisition. However, little attention has been given to the effects of EM and AM species on soil P dynamics and the underlying mechanisms in subtropical forests, where P availability is typically low. To address this knowledge gap, we selected two EM species (Pinus massoniana - PM and Castanopsis carlesii - CC) and two AM species (Cunninghamia lanceolata - Chinese fir, CF and Michelia macclurei - MM) in a common garden established in 2012 in subtropical China. We investigated soil properties (e.g., pH, soil organic carbon, total nitrogen, and dissolved organic nitrogen), soil P fractions, phospholipid fatty acids (PLFAs), enzyme activities, foliar manganese (Mn) concentration, and foliar nutrients and stoichiometry. Our findings revealed that soils hosting EM species had higher levels of resin P, NaHCO3-Pi, extractable Po, total P, and a greater percentage of extractable Po to total P compared to soils with AM species. These results indicate that EM species enhance soil P availability and organic P accumulation in contrast to AM species. Moreover, EM species exhibited higher P return to soil (indicated by higher foliar P concentrations) when compared to AM species, which partly explains higher P accumulation in soils with EM species. Additionally, resin P showed a positive correlation with acid phosphatase (ACP) activity, whereas no correlation was found with foliar Mn concentration, which serves as a proxy for the mobilization of sorbed soil P. Such findings indicate that organic P mineralization has a more substantial impact than inorganic P desorption in influencing P availability in soils hosting both EM and AM species. In summary, our study contributes to a more comprehensive understanding of the effects of mycorrhizal associations on soil P accumulation in subtropical forests and provide valuable insights into plant-soil interactions and their role in P cycling in regions with limited P availability.